Implications of Social Media to the Christians - Emorut Emmanuel (Uganda Christian University, 2025)
Social media serves an integral function in modern day life and serves as a platform for interaction, self-presentation and information sharing. Social media serves as an environment that brings Christians to think how principles derived from the Bible can serve to guide social media usage. The Bible talks about the carefulness of communication and the use of words, particularly that thoughtless words can be dangerous (Prov. 12:18, Jam. 3:6). Also, the division which comes with social media can make it harder for the people within the Church to achieve their goals of spreading love and oneness (1 Corin. 12:25). In relation to these concerns, this research aims to explore the positive and negative impacts of social media on the Christian society in a bid to provide recommendations on how to use social media while abiding by Biblical laws. This is the primary aim of the dissertation, to explore in depth social media’s impact on the Christian man’s life as well as spiritual well-being. In the present era, social media has become an intricate part of life for Christians, providing both positive and negative. On one hand, they have made communicating much easier while on the other, the risk of encouraging thoughtless words is high. Careless speech not only damages relationships but devalues them and can undermine the real bonds that exist traced to community engagement. Consummation of community results in spiritual development and is healthy, but when coupled with online relations where people engage ‘virtually’, it brings about the risk of shallow relationships (Heb. 10:24-25). The ever-growing rate at which false information spreads pose dangers to sound doctrine (1 Thess. 5:21). For example, misinformation and the complexities of the digital landscape will be the focus challenge focus of offer direction for Christians. The design for this research is qualitative and specifically focuses on the social implications of social media among Christians. They are explored through physical libraries and other academic based learning facilities. Qualitative research provides an exploration of the social attitudes and perceptions Christians have on social media such as the spiritual and emotional impacts of social media. The objectives of this research are multi-faceted. They include determining the responsible social media attitudes, evaluating the emotional relational aspects, and assessing the overall wide impact from a biblical perspective. As all other groups in the society, Christians need to address the modern societal challenges that could disengage them from the digital age. This research aims at providing the church with practical solutions that could promote Christians’ togetherness through healthy digital interaction that can help them grow spiritually. The general goals of the church and biblical teachings have to align with the rapidly increasing social media use, making the research particularly helpful and important. The findings of the analysis will contribute to the growing scholarship on technology, digital culture, and Christian discipleship while serving the academic and church communities